Neopheosia pseudofasciata sp. nov., a new species of Notodontidae (Lepidoptera) from Wuyishan National Park, southeastern China - Zhang, Yu-Long; Wang, Min; Ma, Fang-Zhou (Zootaxa, 2022)
A new species of the genus Neopheosia Matsumura, 1920, N. pseudofasciata sp. nov. is described and illustrated from Fujian province. The species resembles N. fasciata (Moore, 1888) but differs in a forewing pattern in M3 cell; diagnostic differences are observed in genitalia characters as well. DNA barcode data of the new species and its relatives are deposited in GenBank. A key to the Neopheosia species based on morphology is presented. The holotype is deposited in the Department of Entomology, College of Plant Protection, South China Agricultural University, Guangzhou.